1996
DOI: 10.1007/bf00185930
|View full text |Cite
|
Sign up to set email alerts
|

Carbon ?-doping GaAs superlattices

Abstract: Carbon 6-doping GaAs superlattices incorporating 50 layers have been grown either by chemical beam epitaxy (CBE) using CBr4 as the source of the carbon or by metallorganic vapour phase epitaxy (MOVPE) using CCI4. Infrared (IR) localized vibrational mode (LVM) spectroscopy showed that carbon atoms were incorporated on the As sublattice and that hydrogen was incorporated as H-CAs pairs during growth by MOVPE. The hydrogen was removed by an anneal at 600°C for 15 min in N2, leading to an increase in the carrier c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…12 Both intrinsic and extrinsic C doping of AlGaAs have been studied by several authors 4,7,8,11,12 who have shown that the C incorporation is more efficient for higher Al content in the alloy and lower growth temperatures (T g ). 6,11,14 In this communication results of a thorough investigation of C delta-doping of AlGaAs grown by MOVPE using CBr 4 as the C source are presented. 7 Another difficulty with the C doping is the passivation of the impurity by H atoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Both intrinsic and extrinsic C doping of AlGaAs have been studied by several authors 4,7,8,11,12 who have shown that the C incorporation is more efficient for higher Al content in the alloy and lower growth temperatures (T g ). 6,11,14 In this communication results of a thorough investigation of C delta-doping of AlGaAs grown by MOVPE using CBr 4 as the C source are presented. 7 Another difficulty with the C doping is the passivation of the impurity by H atoms.…”
mentioning
confidence: 99%
“…6,8,17,18 Points above the solid line correspond to a confinement over a region wider than 5 Å. The squares represent the samples grown for this work, while the other data points refer to results from the GaAs literature.…”
mentioning
confidence: 99%